Conditional survival in patients with stage IB‐IIIA melanoma undergoing sentinel node biopsy in Queensland: A longitudinal study. (18th January 2023) - Tedman, Alexander James; Liyanage, Upekha E.; Chong, Sharene; Rowe, Casey; von Schuckmann, Lena A.; Malt, Maryrose; Green, Adele C.; Smithers, B. Mark; Khosrotehrani, Kiarash
Abstract: Background: Tumour characteristics such as thickness and ulceration, along with sentinel lymph node (SLN) status, have been essential in predicting survival in patients with locally invasive melanomas at the time of diagnosis. It is unclear if these prognostic factors are relevant 1, 2 or 5 years after diagnosis. Objectives: The key aim of this project was to analyse conditional survival in a cohort of Queensland patients with stage IB to IIIA melanomas (American Joint Committee on Cancer's staging system, 8th version) and to test the relevance of clinicopathological prognostic factors for melanoma outcome after varying intervals of survival time. Methods: Patients with primary invasive cutaneous melanoma who were referred to a tertiary melanoma clinic and underwent SLN biopsy between 1994 and 2011 were ascertained. The effect of patient and tumour characteristics on melanoma survival were calculated using multivariate Cox proportional hazard models at diagnosis and at variable times after diagnosis. Results: The final analysis included 651 patients (average age 49 years, 55.5% male) with stage IB to IIIA melanoma. At diagnosis, and after 1 and 2 years survived, SLN positivity, thickness and ulceration were predictive of 10‐year survival since diagnosis. However, once patients survived 5 years, only SLN status was predictive. Overall conditional melanoma survival improved with increasing time survived. Five years after diagnosis, 10‐year conditional melanoma survival (MSS) was 91% (95% CI 86%–95%) compared with 85% (82%–88%) predicted at diagnosis. The improvement in MSS was observed mainly for Stage II melanoma patients and not for those with a positive SLN biopsy. Conclusions: This study confirms the improvement of prognosis according to time survived since diagnosis suggesting that after 5 years survival the classic prognostic indicators may not have the same influence.